Genuinely Wearable Display with a Flexible Battery, a Flexible Display Panel, and a Flexible Printed Circuit. Issue 1 (June 2014) - Tajima, Ryota; Miwa, Takuya; Oguni, Teppei; Hitotsuyanagi, Aya; Miyake, Hiroyuki; Katagiri, Haruki; Okano, Shinya; Goto, Yuugo; Saito, Yumiko; Goto, Junya; Kaneyasu, Makoto; Hiroki, Masaaki; et al.
Abstract To fabricate a genuinely flexible and wearable display with a flexible battery together with a flexible OLED panel and a flexible printed circuit, a flexible lithium ion battery has been developed, and a prototype of a wrist‐wearable display has been fabricated.